2007
DOI: 10.1001/jama.297.17.1901
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Patterns to Differentiate Pancreatic Adenocarcinoma From Normal Pancreas and Chronic Pancreatitis

Abstract: Pancreatic cancer may have a distinct miRNA expression pattern that may differentiate it from normal pancreas and chronic pancreatitis. miRNA expression patterns may be able to distinguish between long- and short-term survivors, but these findings need to be validated in other study populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

41
948
4
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,070 publications
(1,004 citation statements)
references
References 26 publications
41
948
4
11
Order By: Relevance
“…[15][16][17][18][19] In pancreatic adenocarcinomas, the expression of miR-15b, miR-21, miR-95, miR-103, miR-107, miR-148a, miR-155, miR-196a, miR-200, miR-210, miR-217, miR-221, miR-222 and miR-375 are different from tissue of normal pancreas and chronic pancreatitis. 17,[20][21][22][23][24][25][26][27] The results reported by Bloomston et al 20 and Szafranska et al 26 give promises of significant clinical impact of microRNA expression profiles to separate tissue from pancreatic adenocarcinomas from normal pancreas and chronic pancreatitis. The study by Szafranska et al 26 included a combination of two microRNAs (the difference between miR-196a and miR-217) to separate pancreatic adenocarcinomas and chronic pancreatitis (ASURAGEN-test).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…[15][16][17][18][19] In pancreatic adenocarcinomas, the expression of miR-15b, miR-21, miR-95, miR-103, miR-107, miR-148a, miR-155, miR-196a, miR-200, miR-210, miR-217, miR-221, miR-222 and miR-375 are different from tissue of normal pancreas and chronic pancreatitis. 17,[20][21][22][23][24][25][26][27] The results reported by Bloomston et al 20 and Szafranska et al 26 give promises of significant clinical impact of microRNA expression profiles to separate tissue from pancreatic adenocarcinomas from normal pancreas and chronic pancreatitis. The study by Szafranska et al 26 included a combination of two microRNAs (the difference between miR-196a and miR-217) to separate pancreatic adenocarcinomas and chronic pancreatitis (ASURAGEN-test).…”
mentioning
confidence: 96%
“…20,21,23,24 MicroRNAs are stable in formalin-fixed paraffin-embedded samples. 28,29 Tumor cells in pancreatic ductal adenocarcinomas are often located in small groups surrounded by an abundant stromal tissue 30 and information related to microRNAs from the stromal tissue may be lost if micro-dissection is applied.…”
mentioning
confidence: 99%
“…81 miRs had low expression and were categorized as not reliably detected. Interestingly, several miRs previously reported as associated with PDAC including, miR‐221‐3p, 210, ‐23a‐3p, ‐143‐3p, and ‐21‐5p were among those highly expressed in the CTC samples (Figure 4C) 17, 18, 19, 20. Additionally, based on pathway analysis, the top network functions enriched in the profiles were for cancer and organismal injury and abnormalities.…”
mentioning
confidence: 85%
“…Moreover, for the first time we report that PDAC CTC miRNA profiling revealed a trend toward high expression of miRs 17‐5p, 19b‐3p, 320b, and let7a‐5p. Also, miR‐96‐3p, 216b, 155‐5p, 212‐3p, and ‐31‐5p which demonstrated decreased expression have been previously reported to exhibit down regulation in pancreatic cancer 17, 18…”
mentioning
confidence: 95%
“…Profiling of PTC by He et al (2005a) yielded a signature of five miRNAs (which included miR-221, miR-222 and miR-146) that can separate PTC from normal thyroid. Bloomston et al (2007) showed that a signature of 21 upregulated and 4 downregulated miRNAs correctly differentiated pancreatic cancer from benign pancreatic tissue in 90% of samples. In the profile, two commonly malignancyassociated miRNAs, miR-21 and miR-155, were uniquely overexpressed in pancreatic cancer compared to normal pancreas.…”
Section: Introductionmentioning
confidence: 99%